FebriDx for rapid screening of patients with suspected COVID-19 upon hospital admission: systematic literature review and meta-analysis. (May 2022) - Lippi, G.; Nocini, R.; Mattiuzzi, C.; Henry, B.M.
Summary: A systematic literature review and meta-analysis was undertaken of the lateral flow-based FebriDx immunoassay for triaging patients with suspected coronavirus disease 2019 (COVID-19) upon admission to healthcare facilities. An electronic search was conducted in Scopus and Medline using the keywords 'FebriDx' AND 'COVID-19' OR 'SARS-CoV-2', with no language or date (i.e. up to 4 th February 2022) limits, selecting studies where FebriDx was used for triaging patients with suspected COVID-19 in acute care settings, and reporting sufficient data to construct a 2×2 table. Five studies were included in the final analysis, totalling 2309 patients. The pooled diagnostic sensitivity and specificity were 0.91 [95% confidence interval (CI) 0.88–0.93] and 0.92 (95% CI 0.90–0.93), whilst the area under the curve, accuracy and kappa statistics were 0.971 (95% CI 0.962–0.980), 91.4% (95% CI 90.2–92.5%) and 0.762 (95% CI 0.731–0.793), respectively, thus reflecting substantial agreement with reference molecular testing techniques. Negative and positive predictive values were 0.974 (95% CI 0.966–0.981) and 0.742 (95% CI 0.711–0.770), respectively. This pooled analysis demonstrated that FebriDx has clinical value for rapid screening of patients with suspected COVID-19 in acute care settings, especially in regions with high viral circulation in which the pre-test probability is high, and enables prioritization for confirmatory laboratory testing.